FREQUENCY OF CRYPTOSPORIDIUM IN CHILDHOOD DIARRHOEA- IMPORTANCE OF MODIFIED ACID FAST TECHNIQUE - Shoaib, Shaheen; Tauheed, Shoaib; Hafiz, Amtul (Journal of Ayub Medical College Abbottabad, 2003)
Background: One of the important causes of childhood diarrhoea is cryptosporidium, a parasitic pathogen which is usually overlooked. This study was therefore designed to show the importance of modified acid fast stain in the diagnosis of cryptosporidium in childhood diarrhoea. Methods: Stool samples from 300 children with prolonged diarrhoea were examined by modified acid fast staining along with wet mounts in saline and iodine. Results: Out of 300 samples five (1.7%) were diagnosed as positive for cryptosporidium. Conclusion: Results indicate that Cryptospori-diosis exists as a cause of diarrhoeal illness in our society. It was also noted that modified acid fast staining of stool samples is an important, non-invasive and useful diagnostic technique in identification of cryptosporidium. Key words: Cryptosporidium. Childhood diarrhea, Modified acid fast technique